Beyond Endemic Burkitt Lymphoma: Navigating Challenges of Differentiating Childhood Lymphoma Diagnoses Amid Limitations in Pathology Resources in Lilongwe, Malawi. (20th June 2017) - El-Mallawany, Nader Kim; Mutai, Mercy; Mtete, Idah; Gopal, Satish; Stanley, Christopher C.; Wasswa, Peter; Mtunda, Mary; Chasela, Mary; Kamiyango, William; Villiera, Jimmy; Fedoriw, Yuri; Montgomery, Nathan D.; et al.
Background. Although Burkitt lymphoma (BL) is the most common childhood lymphoma in sub-Saharan Africa, Hodgkin lymphoma (HL) and other non-Hodgkin lymphomas occur. Diagnosing non-jaw mass presentations is challenging with limited pathology resources. Procedure. We retrospectively analyzed 114 pediatric lymphomas in Lilongwe, Malawi, from December 2011 to June 2013 and compared clinical versus pathology-based diagnoses over two time periods. Access to pathology resources became more consistent in 2013 compared with 2011-2012; pathology interpretations were based on morphology only. Results. Median age was 8.4 years (2.1-16.3). The most common anatomical sites of presentation were palpable abdominal mass 51%, peripheral lymphadenopathy 35%, and jaw mass 34%. There were 51% jaw masses among clinical diagnoses versus 11% in the pathology-based group ( P < .01), whereas 62% of pathology diagnoses involved peripheral lymphadenopathy versus 16% in the clinical group ( P < .01). The breakdown of clinical diagnoses included BL 85%, lymphoblastic lymphoma (LBL) 9%, HL 4%, and diffuse large B-cell lymphoma (DLBCL) 1%, whereas pathology-based diagnoses included HL 38%, BL 36%, LBL 15%, and DLBCL 11% ( P < .01). Lymphoma diagnosis was pathology confirmed in 19/66 patients (29%) in 2011-2012 and 28/48 (60%) in 2013 ( P < .01). The percentage of non-BL diagnoses was consistent across time periods (35%); however, 14/23 (61%) non-BL diagnoses were pathology confirmed in 2011-2012 versus 16/17 (94%) in 2013. Conclusions. Lymphomas other than Burkitt accounted for 35% of childhood lymphoma diagnoses. Over-reliance on clinical diagnosis for BL was a limitation, but confidence in non-BL diagnoses improved with time as pathology confirmation became standard. Increased awareness of non-BL lymphomas in equatorial Africa is warranted.